Non-Retentive Overdenture Combination with Cu-Sil for Multiple Tooth Loss Rehabilitation - Huda, Hanifah Hasna; Meidarlina, Ista; Kusumadewi , An-Nissa (Jurnal Locus Penelitian dan Pengabdian, 2025)
Preservation of the remaining alveolar ridge is one of the factors in the success of dentures. Preserving the remaining teeth maintains the integrity of the alveolar ridge and proprioceptive of the periodontium. This also has a positive psychological effect on the patient. Overdenture and cu-sil denture can be used as treatment options in cases of patients who have few remaining teeth. This case report aims to describe the use of cu-sil denture and metal coping non-retentive overdenture in terms of improving the retention and stability of removable denture. A 67-year-old man came to the prosthodontic clinic of Rumah Sakit Gigi dan Mulut Pendidikan Universitas Padjadjaran with lost a lot of teeth that made it difficult to eat and disturbed his appearance. The patient wanted to retain the remaining teeth 14 and 13. Preliminary root canal treatment was performed on tooth 14, which had experienced pulp necrosis. Then a single coping cast non-retentive was inserted into tooth 14. Tooth 13 was retained as an abutment, then the area was perforated for cu-sil denture access. After two months of use, the patient was satisfied with the denture. A removable denture using non-retentive overdenture combined with cu-sil denture can improve retention and stability in cases of multiple tooth loss.